Palladium-Catalyzed Asymmetric Allylic Alkylation Strategies for the Synthesis of Acyclic Tetrasubstituted Stereocenters - Trost, Barry M.; Schultz, Johnathan E. (Synthesis, 2019)
Over the past 20 years, the asymmetric synthesis of acyclic tetrasubstituted stereocenters by Pd-catalyzed asymmetric allylic alkylation (Pd-AAA) strategies has seen considerable growth. Despite the inherent difficulty in accessing acyclic tetrasubstituted stereocenters, creative approaches toward this problem have resulted in high stereoinduction on both electrophilic and nucleophilic reaction partners. Much of this chemistry has paved the way for unique solutions in Mo-, Ir-, and Rh-AAA, with many complimentary methods arising due to the unique regiochemical outcomes of AAA outside of Pd catalysis.1 Introduction2 Stereocontrol on Prochiral Electrophiles3 Stereocontrol on Prochiral Nucleophiles4 Temporary Cyclic Pronucleophiles5 Allylic Alkylation with Other Metals6 Conclusions and Outlook
Keywords: allylic alkylation; acyclic stereocontrol; tertiary alcohols; α-tertiary amines; quaternary carbon stereocenters